Preparation method of environment-friendly pigment yellow 150 for inkjet colorant nanoscale
Patent Information
- Application Number
- CN202511847230.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-10-27
AI Technical Summary
但该方法存在不足:铁、锌均为过渡金属,与镍竞争络合,可能导致色相不稳定;铁离子易氧化,影响产品储存稳定性和色光一致性
1.本发明在络合工艺中,镍离子作为3d8构型的过渡金属离子,其d轨道可通过sp3d2或dsp2杂化形成空的杂化轨道,能够接受配体的孤对电子,与偶氮巴比妥酸分子中的偶氮基团氮原子、羰基氧原子、烯醇式羟基氧原子形成稳定的八面体或平面四方型螯合配位键,这种金属-配体络合物的d-d跃迁和金属-配体电荷转移跃迁共同决定了颜料黄150特征的绿光黄色。通过精确控制第一阶段镍离子的投加量(理论络合量的90%-98%),确保镍离子优先、充分地络合进入颜料晶格形成目标色相的颜料主体结构,同时避免过量镍的残留,从根本上解决了传统工艺游离镍含量高的问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of organic pigment technology, and specifically to a method for preparing an environmentally friendly pigment yellow 150 for inkjet color paste at the nanoscale. Background Technology
[0002] Pigment Yellow 150 (CAS: 68511-62-6) is a nickel-containing heterocyclic azo metal complex pigment, chemically named nickel 5,5'-azobisbarbiturate complex. It is greenish-yellow in color and has excellent transparency, lightfastness (7-8 grade), and heat resistance (up to 260℃), making it an ideal yellow pigment for high-end inkjet printing inks.
[0003] With the rapid development of digital printing, textile printing, ceramic decoration and other fields, inkjet printing technology has placed increasingly stringent requirements on pigments. At the same time, environmental regulations are imposing increasingly strict restrictions on heavy metal content, especially on inks used in food packaging and children's products, requiring that the free nickel content in the product be ≤200ppm and the nickel ion concentration in the production wastewater be ≤1.0mg / L.
[0004] The traditional method for preparing Pigment Yellow 150 typically involves diazotization of aminoguanidine carbonate, condensation with barbituric acid, and then complexation with nickel salts. To ensure complete complexation, an excess of 5%-15% nickel chloride is usually used, resulting in a final product with a free nickel content as high as 500-1000 ppm, far exceeding environmental protection requirements. Simultaneously, the nickel ion concentration in the production wastewater exceeds 10 mg / L, necessitating additional wastewater treatment costs.
[0005] Patent CN109762361A discloses a method for preparing Pigment Yellow 150 using a multi-metal complexation method involving iron, zinc, and nickel. This method partially replaces nickel by introducing metals such as iron and zinc, thus reducing the amount of nickel used to some extent. However, this method has drawbacks: iron and zinc are transition metals that compete with nickel for complexation, potentially leading to hue instability; iron ions are easily oxidized, affecting product storage stability and color consistency.
[0006] Therefore, existing technologies cannot simultaneously meet the core requirements of inkjet pigments for low free nickel content and high dispersion stability, and there is an urgent need to develop a new preparation method to solve the above-mentioned technical problems. Summary of the Invention
[0007] Based on the problems existing in the background technology, the present invention provides a method for preparing an environmentally friendly pigment yellow 150 for inkjet color paste at the nanoscale, so that the pigment obtained simultaneously meets the requirements of nanoscale particle size, low free nickel content and high dispersion stability. The resulting product can be directly used in the preparation of inkjet printing ink and inkjet color paste without further dispersion treatment.
[0008] This invention is implemented through the following technical solutions: A method for preparing nanoscale environmentally friendly pigment yellow 150 for inkjet color pastes includes the following steps: (1) Preparation of azobarbituric acid: aminoguanidine carbonate is diazotized and then condensed with barbituric acid to obtain azobarbituric acid; (2) Stepwise complexation reaction of nickel / calcium: First stage: The azobarbituric acid obtained in step (1) is complexed with nickel chloride hexahydrate, melamine and emulsifier at 90-95℃ for 2-3 hours; Second stage: After the first stage is completed, calcium chloride is added and the reaction continues for 0.5-1 hour to obtain the complex product; (3) Nano-grinding: The complex product obtained in step (2) is added to a polymeric dispersant and then wet nano-grinding is performed to obtain Pigment Yellow 150 dispersion slurry, which is then spray-dried to obtain Pigment Yellow 150 dry powder.
[0009] Furthermore, in step (2), the molar ratio of nickel chloride hexahydrate to the barbituric acid coordination unit in azobarbituric acid is (0.45-0.49):1.
[0010] Furthermore, in step (2), the molar ratio of calcium chloride to the barbituric acid coordination unit in azobarbituric acid is (0.01-0.07):1.
[0011] Furthermore, the molecular structure of azobarbituric acid contains two barbituric acid coordination units. In coordination complexation reactions, each barbituric acid unit can act as an independent coordination site to coordinate with a metal ion. Therefore, the "molar ratio of barbituric acid coordination units in azobarbituric acid" mentioned in this invention refers to the molar ratio of the metal salt or melamine to the barbituric acid coordination units, not the molar ratio of the azobarbituric acid molecule. For example, 10g of azobarbituric acid (molecular weight approximately 282g / mol) is equivalent to 0.0355mol of azobarbituric acid molecules, containing 0.071mol of barbituric acid coordination units (i.e., 0.0355 × 2 = 0.071mol).
[0012] Furthermore, in step (2), the complexation reaction temperature in the first stage is 92-95℃ and the reaction time is 2-3 hours; the reaction temperature in the second stage is 92-95℃ and the reaction time is 0.5-1.5 hours.
[0013] Furthermore, in step (3), the polymeric dispersant is a polycarboxylic acid dispersant or a polyurethane dispersant, and the amount of polymeric dispersant used is 3%-8% of the dry basis mass of the pigment in the complex product.
[0014] Furthermore, in step (3), wet nano-grinding is performed using a horizontal sand mill or a high-energy ball mill, with zirconium oxide beads of 0.1-0.3 mm in diameter as the grinding medium, and the grinding time is 2-6 hours.
[0015] Furthermore, in step (3), the slurry solid content in the grinding process is 15-25%, and the grinding temperature is 20-40℃.
[0016] The present invention also discloses a nanoscale environmentally friendly pigment yellow 150 prepared by the above method.
[0017] This invention also discloses the application of the aforementioned nano-scale environmentally friendly pigment yellow 150 in the preparation of inkjet printing inks, digital printing inks, or textile inkjet inks.
[0018] The beneficial effects of this invention are: 1. In the complexation process of this invention, nickel ions serve as 3d... 8 Transition metal ions with this configuration can have their d orbitals accessed via sp... 3 d 2 or DSP 2 Hybridization creates empty hybrid orbitals that can accept lone pairs of electrons from ligands, forming stable octahedral or planar tetragonal chelate coordination bonds with the nitrogen atom, carbonyl oxygen atom, and enol hydroxyl oxygen atom in the azo barbiturate molecule. The dd transitions and charge transfer transitions of this metal-ligand complex jointly determine the characteristic greenish-yellow hue of Pigment Yellow 150. By precisely controlling the amount of nickel ions added in the first stage (90%-98% of the theoretical complexing amount), it is ensured that nickel ions preferentially and fully complex into the pigment lattice to form the main pigment structure of the target hue, while avoiding excessive nickel residue, fundamentally solving the problem of high free nickel content in traditional processes.
[0019] 2. In this invention, calcium ions introduced into the complexation process are alkaline earth metal ions. Their coordination ability is significantly weaker than that of transition metal nickel, and they mainly react with residual uncomplexed coordination sites through ionic bonding. Calcium ions play a triple role in the pigment system: first, they consume residual coordination sites and undergo bonding reactions with a small amount of uncomplexed azobarbituric acid, ensuring complete reaction; second, they form a calcium salt protective layer on the pigment particle surface, reducing particle surface energy and improving particle dispersion performance, creating favorable conditions for subsequent nano-grinding; and third, they act as a pH buffer, maintaining pH stability in the system. Because calcium's coordination ability is much weaker than nickel's, it will not enter the pigment core lattice to replace already complexed nickel ions. Therefore, this stepwise complexation strategy ensures both the stability of the pigment hue and achieves low free nickel content and good surface properties. Simultaneously, the presence of the calcium salt protective layer reduces the surface energy of the pigment particles, making them easier to break down to the nanoscale during grinding, reducing re-agglomeration during the grinding process.
[0020] 3. This invention combines nickel / calcium stepwise complexation with nano-grinding dispersion technology to achieve the triple goals of nanoscale particle size, low free nickel content, and high dispersion stability while maintaining the excellent color performance of Pigment Yellow 150. It solves the environmental hazards and inkjet applicability problems of traditional processes, and provides a technically feasible and economically reasonable new path for the development of pigment-based inkjet inks. Detailed Implementation
[0021] The technical solution of the present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.
[0022] Example 1: Preparation of Pigment Yellow 150, including the following steps: (1) Preparation of azobarbituric acid: Diazotization reaction: Add 85 mL of deionized water to a 500 mL beaker, add 0.04 g of EDTA (0.05%), and stir to dissolve. Add 18.97 g of hydrochloric acid (31%) while stirring, followed by 9.23 g of aminoguanidine carbonate powder. Stir for 90 minutes until completely dissolved, then cool to 0-5°C in an ice bath. Dissolve 4.96 g of sodium nitrite (96%) in 20 mL of deionized water, clarify, and then slowly add it dropwise to the above diazotization reaction, controlling the temperature at 0-5°C. After the addition is complete, continue stirring for 60 minutes. After the reaction is complete, prepare for condensation.
[0023] Condensation reaction: Add 17.35g of barbituric acid to the diazo solution, heat the slurry to 50℃, and keep it at that temperature for 1.5 hours. Adjust the pH to 4.6 with 32% liquid alkali, keep the reaction at that temperature for 2 hours, then heat to 90℃ and keep the reaction at that temperature for 3 hours to produce the material.
[0024] Post-processing: Cool the material to 70℃, filter by suction, and wash the filter cake with 70℃ hot water until the filtrate pH is 6-7 and the conductivity is <100μS / cm (close to pure water). Obtain azobarbituric acid wet filter cake for later use.
[0025] (2) Stepwise complexation reaction of nickel / calcium: First stage: Add the wet filter cake (10g dry) obtained in step (1) to deionized water, stir and slurry until a uniform slurry with a solid content of about 5%; heat the slurry to 95°C, add 8.04g nickel chloride hexahydrate, 8.48g melamine and 0.05g emulsifier S-80 to the slurry, and maintain the reaction at 95°C for 2.5 hours.
[0026] Second stage: After the first stage is completed, add 0.41g of anhydrous calcium chloride to the reaction slurry, stir to dissolve, and continue the reaction at 95℃ for 1 hour. Slowly adjust the pH to 5.5 with 30% potassium hydroxide solution until the material color stabilizes to a standard greenish-yellow. Cool down to 70℃ to obtain the complexed product, namely crude Pigment Yellow 150.
[0027] (3) Nano-grinding: The complex product slurry obtained in step (2) is filtered and washed with hot water at 50°C until the pH of the filtrate is neutral and the conductivity is <100μS / cm, to obtain a crude wet filter cake. The crude wet filter cake is added to the mixing tank, deionized water is added to a solid content of 20%, and Disperbyk-190 dispersant (polycarboxylic acid, amount accounting for 5% of the dry weight of the pigment) is added. The mixture is stirred for 30 minutes to disperse it evenly. The prepared slurry is transferred to a ball mill, 0.2mm zirconia beads are added, the filling rate is 70%, the speed of the ball mill is 800 rpm, the grinding time is 6 hours, the grinding temperature is below 40°C, and wet grinding is performed to obtain Pigment Yellow 150 dispersion slurry. The slurry is spray-dried to obtain Pigment Yellow 150 dry powder.
[0028] Example 2: The difference between this example and Example 1 is that the amounts of nickel chloride hexahydrate and anhydrous calcium chloride in the complexation step were adjusted.
[0029] First stage: Add 7.86g nickel chloride hexahydrate, 8.48g melamine and 0.05g emulsifier S-80, and react at 95℃ for 2.5 hours.
[0030] Second stage: Add 0.50g of anhydrous calcium chloride, react at 95℃ for 1 hour, and adjust the pH to 5.5.
[0031] The remaining steps are the same as in Example 1.
[0032] Example 3: The difference between this example and Example 1 is that the amounts of nickel chloride hexahydrate and anhydrous calcium chloride in the complexation step were adjusted.
[0033] First stage: Add 8.10g nickel chloride hexahydrate, 8.48g melamine and 0.05g emulsifier S-80, and react at 95℃ for 2.5 hours.
[0034] Second stage: Add 0.33g of anhydrous calcium chloride, react at 95℃ for 1 hour, and adjust the pH to 5.5.
[0035] The remaining steps are the same as in Example 1.
[0036] Comparative Example 1: Using the traditional excess nickel process.
[0037] In the complexation step, 9.27g of nickel chloride hexahydrate (10% excess), 8.48g of melamine and 0.05g of emulsifier S-80 were added at once. The mixture was reacted at 95℃ for 3 hours. The pH was adjusted to 5.5 with potassium hydroxide solution and kept at this temperature for 0.5 hours. Water was then added and the temperature was lowered to 70℃ to obtain the complexed product, namely crude Pigment Yellow 150.
[0038] The remaining steps are the same as in Example 1.
[0039] Comparative Example 2: A multi-metal simultaneous complexation process was adopted.
[0040] In the complexation step, 7.98 g of nickel chloride hexahydrate, 0.023 g of zinc chloride, 0.034 g of ferrous chloride tetrahydrate, 8.48 g of melamine, and 0.05 g of emulsifier S-80 were added simultaneously and reacted with azobarbituric acid at 95°C for 3 hours. The remaining steps were the same as in Example 1.
[0041] Experimental example: Performance tests were conducted on the pigment yellow 150 prepared in the examples and comparative examples.
[0042] 1. Particle size distribution: determined using a laser particle size analyzer. The sample was dispersed in deionized water, sonicated for 60 seconds, with the opacity controlled at 10-20%. Each sample was tested 3 times, and the average value was taken.
[0043] 2. Free Nickel Content: Accurately weigh 1.00 g of pigment sample (dry basis), add 50 mL of deionized water, stir and extract at 80 °C for 2 hours, and filter. Determine the nickel ion concentration of the filtrate by inductively coupled plasma optical emission spectrometry (ICP-OES) and calculate the free nickel content (ppm).
[0044] 3. Nickel content in wastewater: The washing wastewater after the complexation reaction was filtered through a 0.45 μm filter membrane, and the nickel ion concentration (mg / L) was determined by ICP-OES.
[0045] 4. Storage Stability: The pigment was prepared as a dispersion (10% solid content) and stored in sealed glass bottles at 25℃ and 50℃, respectively. Sampling was performed periodically to measure particle size changes and sedimentation. The observation period was 6 months. Storage stability was evaluated by the particle size growth rate after 6 months. Particle size growth rate (%) = [(particle size after storage - initial particle size) / initial particle size] × 100%.
[0046] 5. Tinting strength: The relative tinting strength of the samples was determined according to the HG / T 3851 standard method, with the tinting strength of Comparative Example 1 sample as 100%.
[0047] 6. Hue Characterization: L was measured using a spectrophotometer. * a * b *Color space values. The pigment was prepared as an aqueous dispersion (5% solids content), coated onto a standard white plate, and measured after drying. △E* ab This indicates the color difference compared to the sample in Comparative Example 1.
[0048] 7. Inkjet compatibility: (1) Viscosity: The pigment was made into ink (pigment content 5%) and the viscosity was measured using a rotational viscometer (Brookfield DV2T) at 25°C and 100 rpm.
[0049] (2) Printhead clogging rate: Load ink into a standard inkjet printhead (nozzle diameter 30μm), spray continuously for 100 cycles (10 minutes each time), record the number of cloggings, and calculate the clogging rate.
[0050] 8. Lightfastness: According to ISO 105-B02 standard, the pigment was prepared into a coating sample and irradiated in a xenon lamp aging chamber with a light intensity of 550W / m². 2 (300-400nm), temperature 45±5℃, relative humidity 50±10%, after 500 hours of continuous exposure. Using the blue wool standard as a reference, the color change level is rated (1-8, level 8 is the best).
[0051] The test results are shown in Table 1.
[0052] Table 1. Test results of Pigment Yellow 150 prepared in the examples and comparative examples. As shown in Table 1, the Pigment Yellow 150 prepared in this embodiment of the invention has a particle size distribution of D50≤120nm and D90≤180nm, meeting the nanoscale requirements and suitable for inkjet printing applications. The free nickel content and the nickel content in the wastewater also meet the requirements of environmental protection laws (free nickel ≤200ppm, wastewater nickel ≤1.0mg / L). In the storage stability test, the particle size increase rate was ≤9.8% after 6 months of storage at 25℃ and ≤17.5% at 50℃, indicating good stability of the dispersion system. The tinting strength is slightly higher than that of Pigment Yellow 150 prepared by traditional processes, and the color difference ΔE* is... ab The viscosity was ≤1.1, demonstrating good hue stability. The prepared ink had a viscosity of 10.8-14.2 mPa·s and a printhead clogging rate of ≤3%, fully meeting the requirements of inkjet printing for rheological properties and jetting stability. In summary, the Pigment Yellow 150 prepared in this example significantly reduced free nickel content and nickel emissions in wastewater while maintaining excellent color performance, achieving a balance between environmental protection and performance.
[0053] Comparative Example 1 used a traditional excess nickel process (10% excess nickel), adding nickel chloride hexahydrate in a single addition for a complexation reaction. The resulting Pigment Yellow 150 pigment had a free nickel content as high as 820 ppm, exceeding environmental limits. The wastewater nickel content reached 15.8 mg / L, requiring significant wastewater treatment costs. Storage stability was poor; at 25℃ and 50℃, the particle size increase rate after 6 months was as high as 18.5% and 35.8%, respectively, approaching or exceeding one-third of the initial particle size, indicating high particle surface energy and easy agglomeration. The ink viscosity was 25.8 mPa·s, and the printhead clogging rate reached 15%, severely affecting inkjet stability and production efficiency.
[0054] Comparative Example 2 employed a multi-metal simultaneous complexation process, adding nickel, zinc, and iron salts simultaneously to react with azobarbituric acid. Although the nickel content was reduced to 6.25g, the introduction of other metal ions resulted in a particle size distribution of D50=138nm and D90=218nm, indicating that the disordered competition caused by multi-metal complexation is detrimental to uniform particle growth and refinement. The free nickel content was 285ppm, lower than Comparative Example 1, but still exceeding the 200ppm limit. Due to the introduction of iron and zinc, the free nickel content of these metals needs further monitoring. The wastewater nickel content was 1.2mg / L, slightly exceeding the standard. Storage stability was poor; the particle size growth rates at 25℃ and 50℃ over 6 months were 22.3% and 41.2%, respectively, with the latter exceeding 40%. Significant sedimentation and color difference changes would occur in practical applications. The ink viscosity was 28.6mPa·s, and the printhead clogging rate was 18%, indicating poor inkjet adaptability. The lightfastness dropped to level 6-7, which may be related to the easy oxidation of iron ions and their poor photochemical stability. The results of Comparative Example 2 show that although the multi-metal substitution strategy can theoretically reduce the amount of nickel used, the resulting problems such as unstable hue, poor storage, and low application performance make it unsuitable as a method for preparing inkjet pigments.
[0055] Finally, it should be noted that the above embodiments are merely illustrative of several implementations of the present invention and are not intended to limit the scope of the invention. For those skilled in the art, any modifications, equivalent substitutions, or improvements made without departing from the concept of the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing nanoscale environmentally friendly pigment Yellow 150 for inkjet color pastes, characterized in that, Includes the following steps: (1) Preparation of azobarbituric acid: aminoguanidine carbonate is diazotized and then condensed with barbituric acid to obtain azobarbituric acid; (2) Stepwise complexation reaction of nickel / calcium: First stage: The azobarbituric acid obtained in step (1) is complexed with nickel chloride hexahydrate, melamine and emulsifier at 90-95℃ for 2-3 hours; Second stage: After the first stage is completed, calcium chloride is added and the reaction continues for 0.5-1 hour to obtain the complex product; (3) Nano-grinding: The complex product obtained in step (2) is added to a polymeric dispersant and then wet nano-grinding is performed to obtain Pigment Yellow 150 dispersion slurry, which is then spray-dried to obtain Pigment Yellow 150 dry powder.
2. The preparation method according to claim 1, characterized in that, In step (2), the molar ratio of nickel chloride hexahydrate to the barbituric acid coordination unit in azobarbituric acid is (0.45-0.49):
1.
3. The preparation method according to claim 1, characterized in that, In step (2), the molar ratio of calcium chloride to barbituric acid coordination units in azobarbituric acid is (0.01-0.07):
1.
4. The preparation method according to claim 1, characterized in that, In step (2), the complexation reaction temperature in the first stage is 92-95℃ and the reaction time is 2-3 hours; the reaction temperature in the second stage is 92-95℃ and the reaction time is 0.5-1.5 hours.
5. The preparation method according to claim 1, characterized in that, In step (3), the polymeric dispersant is a polycarboxylic acid dispersant or a polyurethane dispersant.
6. The preparation method according to claim 1, characterized in that, In step (3), the amount of polymeric dispersant used is 3%-8% of the dry basis mass of the pigment in the complexed product.
7. The preparation method according to claim 1, characterized in that, In step (3), wet nano-grinding is performed using a horizontal sand mill or a high-energy ball mill, with zirconium oxide beads of 0.1-0.3 mm in diameter as the grinding media, and the grinding time is 2-6 hours.
8. The preparation method according to claim 1, characterized in that, In step (3), the slurry solid content in the grinding process is 15%-25%, and the grinding temperature is controlled at 20-40℃.
9. A nanoscale environmentally friendly pigment yellow 150 prepared by the method described in any one of claims 1-8.
10. The application of the nano-grade environmentally friendly pigment yellow 150 according to claim 9 in the preparation of inkjet printing ink, digital printing ink or textile inkjet ink.
Citation Information
Patent Citations
Preparation method of pigment yellow 150
CN109762361A